Larval fish assemblages from channels and fjords of south Pacific Patagonia: effects of environmental conditions (Revista de Biología Marina y Oceanografía, 2018)
Chilean Patagonian fjords are characterized by strong stratification and chemical gradients which influence the ichthyoplankton distribution and abundance. Plankton samples were collected through bongo net oblique tows in 40 stations from onboard a bio-oceanographic cruise took place in inner fjords of southern Chile (47° to 51°S). Water column physical data were obtained with a conductivity-temperature-depth profiler (CTD) and turbidity was measured with a portable turbidimeter from 0 to 100 m depth. Stations were distributed by three zones: oceanic, channels and continental waters. A total of 1424 larvae were collected, representing 21 families. Dominant taxa were Maurolicus parvipinnis (31%), Sebastes oculatus (12%), Merluccius australis (11%), Lampanyctodes hectoris (10%), and Bathylagichthys parini (8%). Most of the environmental variability was determined by salinity, mainly in the area where continental waters are discharged. The water column in the oceanic zone presented mixed waters dominated by the myctophid L. hectoris and the sternoptychid M. parvipinnis. No significant effect of turbidity gradients on larval fish assemblages was evident during spring. The channel zone was both more saline, and density stratified with less turbidity, and lower abundance of species. Two ichthyoplanktonic assemblages were evident, one living in oceanic waters, and the other from channels and inner zones.